Evaluating the effectiveness of propylene glycol and ethanol as antifreeze: an environmentally friendly alternative - Bhattarai, Bikas Chandra; Parajuli, Achut; Stiansen-Snoerud, Kjetil Bertin (Frontiers in Environmental Engineering, 2025)
Accurate measurement of solid precipitation still remains a significant challenge especially in snow dominated regions. Although it seems straightforward to measure solid precipitation by installing a simple gauge, measurement uncertainty remains the limiting factor even for the sophisticated precipitation collector. Precipitation gauges often rely on an antifreeze solutions, mostly ethylene glycol and methanol (glycometh), to melt snow stored in the collector and provide solid precipitation measurements. However, using antifreeze solution like glycometh often leads to various health and environmental issues. This study evaluates the effectiveness of propylene glycol and ethanol as an environmentally friendly alternatives of glycometh. Furthermore, our study examines the effectiveness of antifreeze mixtures and oil types suitable for the frigid cold temperatures. Based on our analysis, a mixture of 50% propylene glycol (PG) and 50% ethanol (E) solution demonstrated promising efficacy and remained in liquid state even at colder temperature of −40°C, thereby allowing significant dilution. Hydraulic oil is often used atop the antifreeze mixture to prevent evaporation loss from the precipitation. Moreover, some environmental concerns and toxicity risks are associated with the use of such oil. Therefore, we performed further test using Anderol’s food-grade synthetic oil as a safer alternative. The outcome of this test was promising and use of synthetic oil proved to be a viable, environmentally safe alternative for reliable precipitation measurements in cold climates.